Incidental infestations of humans by hard ticks (Acari: Ixodidae) in Colombia: Case reports and record of Amblyomma cajennense sensu stricto - Vargas-Martínez, Omar Esteban; Naranjo-Vargas, Luisa Fernanda; Aramendiz-Macías, Laura; Díaz, Francisco J.; Quintero-Vélez, Juan Carlos; Martins, Thiago Fernandes; Rodas-González, Juan David (Ticks and tick-borne diseases, 2025)
In Colombia, there are few studies that describe tick parasitism in humans, as well as its demographic and ecological characteristics. Additionally, multiple cases of human rickettsiosis caused by highly pathogenic Rickettsia species have been reported, whose vector remains unknown. This study reports new cases of human infestation by hard ticks in rural areas of different municipalities of Colombia between 2021 and 2023. The collected ticks were identified using taxonomic keys and molecular and phylogenetic analyses. Likewise, geographical data and other variables associated with parasitism were recorded. A total of 17 hard ticks were collected, associated with 15 infestation cases from nine individuals in eight municipalities across four departments of Colombia. Our findings included infestations by Amblyomma cajennense sensu stricto [s.s.] in the department of Meta, a species never reported in Colombia, and Amblyomma oblongoguttatum in Antioquia, not reported in humans since 1949. We also report cases of human parasitism by Amblyomma mixtum, Dermacentor nitens, and Rhipicephalus microplus. No Rickettsia bacteria were detected in the ticks. This study highlights the importance of recording the interaction of these ectoparasites with humans in Colombia, expanding knowledge about the diversity of tick species and their parasitic activity in our country.